Nutritional Status and Health Risk Assessment: A Study among the Angami Tribal Adults of Kohima, Nagaland (Indian Journal of Public Health Research & Development, 2021)
Background: Recent developmental activities with increasing urbanization has brought about immensechanges in the lifestyles of tribal populations in India. But their impact on the health and nutritional statusremained poorly explored.Objectives: This study explored the nutritional and health status of the Angami tribal adults, and theinfluence of income, alcohol and tobacco use.Method: Cross-sectional data of 565 individuals from the age of 21–60 years were collected for this study.Nutritional and health status was assessed using BMI, WHR and WHtR.Results: Underweight was more prevalent in the females (12.7%),whereas, overweight (19.7%) and obese(23.1%) were more prevalent in the males. Risk for cardiovascular disease and metabolic abnormalitiesbased on WHR and WHtR are higher in the females. Chi-square analysis showed significant difference inthe nutritional and health status between sex and age groups.Conclusion: Nutritional status according to BMI showed that males have a better status of nutrition. Thereis an increasing prevalence of overweight and obesity along with increased risk of for cardiovascular diseaseand metabolic abnormalities with increasing age. Income, alcohol and tobacco use did not correlate withsignificantly with nutritional status and health risk in females.
Keywords: Nutritional status, undernutrition, overweight, obese, cardio-metabolic abnormalities.